Practical Skills for Tour Guides Tourism Service Vocational School Students Face the Dynamics of Labor Demand in the Tourism Industry - Trinanti; Nurhadi, Didik; Nurjanah, Nunung (EDUTEC : Journal of Education And Technology, 2025)
This qualitative study analyzes the development of practical tour guide skills among vocational high school students based on Kolb's Experiential Learning Theory (Pondok & Nurul, 2021) . Through interviews, observations, and document studies, a significant gap was found between the curriculum, which focuses on guiding techniques, and the industry's need for soft skills such as interpersonal communication, problem solving, and adaptability (Firdausia, 2025) . The implementation of the Kolb cycle, particularly the reflection and active experimentation stages post-work practice, was identified as suboptimal, resulting in graduates' competencies not fully aligning with the rapidly evolving dynamics of the tourism industry.